2020
DOI: 10.1186/s12887-020-1970-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of Salmonella and Shigella species isolated from diarrheic children in Ambo town

Abstract: Background: Diarrhea, particularly of enteric bacterial pathogen, remains a major cause of morbidity and mortality in Ethiopia. Despite the high prevalence of diarrheal disease among under-five children, antibiotic resistance of bacterial pathogens test is not part of routine childcare in the study area. This study aimed to investigate the prevalence and antimicrobial susceptibility status of Salmonella and Shigella species among diarrheic children attending public health institutions in Ambo town, west Showa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
21
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 25 publications
10
21
15
Order By: Relevance
“…Furthermore, 86.2% of S. Typhi strains were found to be resistant to amikacin (Table -2). Studies conducted in India and Ethiopia demonstrated the susceptibility of S. Typhi to amikacin [42,43], which is not in agreement with our results. S. Typhi strains (96.5%) were found to be resistant to gentamicin (MIC≤1) (Table -2), which is not in accordance with previous reports that showed a susceptibility of S. Typhi to gentamicin [25,43].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 86.2% of S. Typhi strains were found to be resistant to amikacin (Table -2). Studies conducted in India and Ethiopia demonstrated the susceptibility of S. Typhi to amikacin [42,43], which is not in agreement with our results. S. Typhi strains (96.5%) were found to be resistant to gentamicin (MIC≤1) (Table -2), which is not in accordance with previous reports that showed a susceptibility of S. Typhi to gentamicin [25,43].…”
Section: Discussioncontrasting
confidence: 99%
“…Studies conducted in India and Ethiopia demonstrated the susceptibility of S. Typhi to amikacin [42,43], which is not in agreement with our results. S. Typhi strains (96.5%) were found to be resistant to gentamicin (MIC≤1) (Table -2), which is not in accordance with previous reports that showed a susceptibility of S. Typhi to gentamicin [25,43]. Moreover, recent data reported that Gram-negative bacteria were sensitive to gentamicin [40].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…All the Salmonella isolates showed resistance to ampicillin. This result is in line with earlier Ethiopian studies [ 38 , 39 ]. In addition, 66% Salmonella spp.…”
Section: Discussionsupporting
confidence: 94%
“…isolates exhibited resistance to both cotrimoxazole and tetracycline. This is in line with results documented in earlier studies performed in various regions of the country [ [38] , [39] , [40] , [41] ]. According to the WHO, MDR exhibited by species of Salmonella is currently a serious global concern.…”
Section: Discussionsupporting
confidence: 93%